DEVELOPMENT OF A PASTORAL MODEL FOR THE ELDERLY IN AN EFFORT TO PROVIDE THE SPIRIT OF LIFE AT THE GRAHA WERDHA MARIE JOSEPH PONTIANAK NURSING HOME - Adi Ria Singir Meliyanto (Jurnal Scientia, 2023)
Thanks to the gift of life, humans can live to a ripe old age. The elderly who have been placed in nursing homes are expected to be able to continue to have the motivation to live their lives as normal humans. The purpose of the study is to explain the current implementation of pastoral care for the elderly by the counselor in an effort to give his life spirit, to explain the design of a pastoral model that is appropriate for the mentor, to explain the level of applicability of the pastoral model design that is produced, which is seen from the aspects: the spirit of the elderly's life; support for the implementation of elderly companions; the substance of the content and flexibility of the model design structure; alignment with support tools and materials; potential stakeholder support, explaining the impact of implementing the resulting pastoral model on aspects: the spirit of life, support for the implementation of the duties of the elderly companion, especially in preparing the pastoral plan for the elderly, carrying out pastoral care for the elderly, and evaluating the pastoral outcomes of the elderly. The author uses research and development methods (Research and Development / R & D). The writing concludes that the current pastoral practices for the elderly, such as: the Rosary, the Koronka, and praying for the elderly who are nearing death, the Eucharist Celebration, the Sacrament of Holy Oil for the elderly in need. The design of the worship model for the elderly has a very good level of applicability. The implementation of worship went smoothly with high interest in the participation of the elderly, carried out in solemn conditions and made the elderly carried away in an atmosphere of worship in such a way as to draw closer to God. The model of worship of the word, really supports the implementation of the duties of the elderly companion and in the preparation of pastoral plans can be arranged in a practical and more efficient manner. Parents who are happy and happy in their daily lives will continue to live their lives with a peaceful heart and surrender to God's will.